Polyvinylidene Fluoride and Polyetherimide Hollow Fiber Membranes for CO2 Stripping in Membrane Contactor - Rosmawati, Naim; Ahmad Fauzi, Ismail; N. B., Cheer; M. S., Abdullah (Elsevier Ltd, 2013)
Porous polyvinylidene fluoride (PVDF) and polyetherimide (PEI) hollow fiber membranes incorporating polyethylene glycol (PEG) were prepared via spinning process for CO2 membrane stripping. CO2 loaded diethanolamine solution was used as liquid absorbent while N2 was used as a strip gas. The characterization study of the fibers was carried out in terms of permeation test, contact angle measurement and liquid entry pressure (wetting pressure). Performance study via membrane contactor stripping was carried out at specific operating condition. The experimental results showed that PVDF membrane have high gas permeation, effective surface porosity and contact angle despite having lower liquid entry pressure in comparison with PEI membrane. PVDF-PEG membrane showed the highest stripping flux of 4.0 × 10−2 mol m−2 s−1 at 0.7 ms−1 compared to that of PEI membrane. Although the stripping flux for PEI-PEG membranes was slightly lower than PVDF membrane (e.g. 3.5 × 10−2 mol m−2 s−1 at liquid velocity of 0.85 ms−1), the membrane wetting pressure of PEI membrane is higher than hydrophobic PVDF membrane. Long term performance of both membranes showed severe flux reduction but started to level-off after 30 h of operation.